Extracorporeal LDL cholesterol elimination (25 years of experience in CZ) - Blaha, M; Zadak, Z; Blaha, V; Andrys, C; Havel, E; Vyroubal, P; Blazek, M; Filip, S; Lanska, M; Maly, J (Atherosclerosis. Supplements, 2009)
In the Czech Republic the therapy of severe familial hypercholesterolemia (FH) by extracorporeal elimination using LDL-apheresis (immunoadsorption) and hemorheopheresis is concentrated into one center. The authors evaluate the long-term therapy (3-12 years, median 7,25) in 12 patients with FH - 3 homozygous, 9 heterozygous; Fredrickson type IIa, IIb (treated: 9 by LDL-apheresis and 3 by hemorheopheresis). Immunoapheretic interventions decrease LDL-cholesterol, ApoB and even Lp(a) by about 82 +/- 1; 73 +/- 13; 82 +/- 19 %, respectively. Selected non-invasive methods are important for a long-term and repeated follow-up. Carotid intima-media thickness showed improvement or stagnation in 75% of the patients. The level of some adhesive molecules, cytokines, endoglin and some coagulation functions were measured, but no universally accepted biomarkers informing of the actual activity of the disease were found to predict and plan the therapy. A program for procedure planning with the use of Microsoft® Excel for Windows® was developed. In summary, LDL-apheresis and hemorheopheresis substantially lower LDL-cholesterol in FH. Our experience with long-term therapy also shows good tolerance and a small number of complications (5,6% of clinically irrelevant side-effects). Hemorheopheresis may improve blood flow in microcirculation in familial hypercholesterolemia and also in some other disorders of microcirculation.
Keywords: imunosorpční techniky; hyperlipoproteinemie typ II; Cholesterol, LDL; Humans; Immunosorbent Techniques; výsledek terapie; Therapy, Computer-Assisted; Blood Component Removal; lidé; Biomarkers; Hyperlipoproteinemia Type II; LDL-cholesterol; časové faktory; separace krevních složek; počítačem asistovaná terapie; biologické markery; Treatment Outcome; Czech Republic; Česká republika; nemoci arterie carotis; Carotid Artery Diseases; Time Factors